2022
DOI: 10.1103/physrevlett.129.145901
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement and Saturation of Near-Field Radiative Heat Transfer in Nanogaps between Metallic Surfaces

Abstract: Detailed spectroscopy of the neutron-deficient nucleus 36 Ca was obtained up to 9 MeV using the 37

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…These confined phonon–photon coupled surface waves have enhanced near-field thermal radiation, which can even exceed the blackbody limits. 27–29 Our previous study reported 8.5× higher emissivity of SiO 2 nanoribbons compared to a thin film with an otherwise similar structure. The enhancement stemmed from a strong resonance at thermal wavelengths.…”
Section: Introductionmentioning
confidence: 91%
“…These confined phonon–photon coupled surface waves have enhanced near-field thermal radiation, which can even exceed the blackbody limits. 27–29 Our previous study reported 8.5× higher emissivity of SiO 2 nanoribbons compared to a thin film with an otherwise similar structure. The enhancement stemmed from a strong resonance at thermal wavelengths.…”
Section: Introductionmentioning
confidence: 91%
“…To measure the radiative heat flow between the emitter and receiver, we started experiments using devices coated with 50 nm thick MgF 2 films. The devices were precisely aligned using the custom-built nanopositioner (detailed procedure can be found in our previous works ,, ) and then maintained at a high vacuum of ∼1 μTorr to minimize thermal transport via air conduction and convection. The emitter is heated to a temperature T e above the temperature of the receiver, T r , by passing a DC current through the platinum heater.…”
Section: Experimental Schemementioning
confidence: 99%
“…In contrast, research on near-field radiative heat transfer (NFRHT) has only recently begun to gain momentum, owing to the rapid advancement of nanoscience and nanotechnology. NFRHT refers to the scenario when the separation (gap) between a hot emitter and a cold receiver is comparable to or smaller than the characteristic thermal wavelength, and holds great potential for a variety of applications such as thermophotovoltaics, photonic refrigeration, , and thermal diodes. Recent experiments have unambiguously demonstrated that thermal radiation at the nanoscale is profoundly different from that in the far field and can achieve heat transfer rates exceeding the blackbody limit by a few orders of magnitude. Many studies have also focused on enhancing and manipulating NFRHT with metals and dielectrics, metamaterials, and multilayer thin-film structures. ,, In particular, tuning NFRHT via thin films is critical for performance enhancements in thermal rectification, energy conversion, and heat-assisted magnetic recording . However, to date, thermal radiation of thin films in nanometer gaps remains largely experimentally unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…It is theoretically shown that metamaterials made of nanoparticles of polaritonic materials can emit localized surface phonons (LSPhs) in their Reststrahlen band, causing narrow-band peaks in the near-field spectra. ,, It is proposed that the spectral location of the thermally emitted LSPhs can be modulated by varying the size and shape of the nanoparticles. ,, Tuning the spectrum of far-field thermal radiation by engineering the geometry of the polaritonic metamaterials has been demonstrated experimentally. , However, near-field thermal emission of LSPhs from polaritonic metamaterials has not been experimentally demonstrated yet. Indeed, while there have been several experimental studies on total (spectrally-integrated) near-field radiative heat transfer, ,,, measurements of the spectrum of near-field thermal radiation have been scarce. , A limited number of studies have experimentally explored the near-field response of polaritonic metamaterials to an external illumination using scattering-scanning near-field optical microscopy (sSNOM). ,, Using sSNOM, an external infrared electromagnetic field is shined to an AFM tip which is located at a subwavelength distance from the metamaterials. The backscattered field from the AFM tip is guided to a Fourier transform infrared spectrometer to determine the near-field response of the metamaterials.…”
Section: Introductionmentioning
confidence: 99%